Proinflammatory Effects of Diesel Exhaust Nanoparticles on Scleroderma Skin Cells. (1st June 2014) - Mastrofrancesco, A.; Alfè, M.; Rosato, E.; Gargiulo, V.; Beatrice, C.; Di Blasio, G.; Zhang, B.; Su, D. S.; Picardo, M.; Fiorito, S.
Abstract : Autoimmune diseases are complex disorders of unknown etiology thought to result from interactions between genetic and environmental factors. We aimed to verify whether environmental pollution from diesel engine exhaust nanoparticulate (DEP) of actually operating vehicles could play a role in the development of a rare immune-mediated disease, systemic sclerosis (SSc), in which the pathogenetic role of environment has been highlighted. The effects of carbon-based nanoparticulate collected at the exhaust of newer (Euro 5) and older (Euro 4) diesel engines on SSc skin keratinocytes and fibroblasts were evaluated in vitro by assessing the mRNA expression of inflammatory cytokines (IL-1 α, IL-6, IL-8, and TNF- α ) and fibroblast chemical mediators (metalloproteases 2, 3, 7, 9, and 12; collagen types I and III; VEGF). DEP was shown to stimulate cytokine gene expression at a higher extent in SSc keratinocytes versus normal cells. Moreover, the mRNA gene expression of all MMPs, collagen types, and VEGF genes was significantly higher in untreated SSc fibroblasts versus controls. Euro 5 particle exposure increased the mRNA expression of MMP-2, -7, and -9 in SSc fibroblasts in a dose dependent manner and only at the highest concentration in normal cells. We suggest that environmental DEP could trigger the development of SSc acting on genetically hyperreactive cell systems.